THE PSYCHOLINGUISTIC IMPACT OF VOICE ASSISTANTS AND DIGITAL AUDIO CONTENT ON EARLY CHILDHOOD LANGUAGE DEVELOPMENT (Eureka Journal of Language, Culture & Social Change, 2026)
The rapid integration of digital technologies into everyday life has significantly transformed the linguistic environment in which children acquire language. This study investigates the psycholinguistic impact of voice assistants, animated digital content, and prerecorded audio input on early childhood language development. Drawing on sociocultural and cognitive psycholinguistic frameworks, the research examines how artificial auditory input influences lexical acquisition, pragmatic competence, and dialogic language skills in children aged 4-6. Using observational data, parental questionnaires, and controlled language tasks, the study reveals that while digital audio exposure may enhance receptive vocabulary, it may simultaneously constrain interactive and pragmatic language development. The findings contribute to contemporary debates on language acquisition in technologically mediated environments and offer implications for psycholinguistic theory and educational practice.
Keywords: Psycholinguistics, child language development, voice assistants, digital media, artificial speech input.